Schools’ Strengths and Areas for Improvement: Perspectives From External Evaluation Reports - Seabra, Filipa; Henriques, Susana; Mouraz, Ana; Abelha, Marta; Tavares, Ana (Frontiers in Education, 2022)
In the context of schools’ growing autonomy, external evaluation mechanisms, including External Evaluation of Schools (EES), are increasingly central to educational policies. This paper is based on the documentary analysis of all reports of the third cycle of EES in Portugal (77 reports), focusing on two of the sections of those reports—the strengths and areas for improvement identified in them. The analysis intends to uncover the areas EES is currently stressing as relevant to assess schools’ quality and identify tendencies across years of implementation and territorial areas (TAs). The results identify some impacts from the TAs, highlighting the effects of the agents interpreting and implementing the policies. Some areas are highlighted as critical—such as the impact of self-evaluation, management, curriculum management, supervision and accompaniment of teaching practices, evaluation, pedagogical practices, or the analysis and improvement of the results. These areas are aligned with broader educational policy priorities.